Determinants of completion of advance directives: a cross-sectional comparison of 649 outpatients from private practices versus 2158 outpatients from a university clinic. Issue 12 (21st December 2017) - Pfirstinger, Jochen; Bleyer, Bernhard; Blum, Christian; Rechenmacher, Michael; Wiese, Christoph H; Gruber, Hans
Abstract : Objectives: To compare outpatients from private practices and outpatients from a university clinic regarding the determinants of completion of advance directives (AD) in order to generalise results of studies from one setting to the other. Five determinants of completion of AD were studied: familiarity with AD, source of information about AD, prior experiences with own life-threatening diseases or family members in need of care and motives in favour and against completion of AD. Design: Observational cross-sectional study. Setting: Private practices and a university clinic in Germany in 2012. Participants: 649 outpatients from private practices and 2158 outpatients from 10 departments of a university clinic. Outcome measures: Completion of AD, familiarity with AD, sources of information about AD (consultation), prior experiences (with own life-threatening disease and family members in need of care), motives in favour of or against completion of AD, sociodemographic data. Results: Determinants of completion of AD did not differ between outpatients from private practices versus university clinic outpatients. Prior experience with severe disease led to a significantly higher rate of completion of AD (33%/36% with vs 24%/24% without prior experience). Participants with completion of AD had more often received legal than medical consultation before completion, but participants without completion of AD are rather aiming for medical consultation. The motives in favour of or against completion of AD indicated inconsistent patterns. Conclusions: Determinants of completion of AD are comparable in outpatients from private practices and outpatients from a university clinic. Generalisations from university clinic samples towards a broader context thus seem to be legitimate. Only one-third of patients with prior experience with own life-threatening diseases or family members in need of care had completed an AD as expression of their autonomous volition. The participants' motives for or against completion of AD indicate that ADs are considered a kind of 'negative autonomy' as instruments to prevent particular forms of therapy. Interactive, repeated and situation-based AD discussions might reach a higher percentage of patients and concurrently enable personal volitions and thereby strengthen individual 'positive autonomy'.